Pharmacological modulation of myeloid-derived suppressor cells to dampen inflammation - van Geffen, Chiel; Heiss, Constantin; Deißler, Astrid; Kolahian, Saeed (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous cell population with potent suppressive and regulative properties. MDSCs’ strong immunosuppressive potential creates new possibilities to treat chronic inflammation and autoimmune diseases or induce tolerance towards transplantation. Here, we summarize and critically discuss different pharmacological approaches which modulate the generation, activation, and recruitment of MDSCs in vitro and in vivo, and their potential role in future immunosuppressive therapy.